A Review On Application Of Chitosan As A Natural Antimicrobial - F. Nejati Hafdani; N. Sadeghinia (Zenodo, 2011)
In recent years application of natural antimicrobials instead of conventional ones, due to their hazardous effects on health, has got serious attentions. On the basis of the results of different studies, chitosan, a natural bio-degradable and non-toxic biopolysaccharide derived from chitin, has potential to be used as a natural antimicrobial. Chitosan has exhibited high antimicrobial activity against a wide variety of pathogenic and spoilage microorganisms, including fungi, and Gram-positive and Gramnegative bacteria. The antimicrobial action is influenced by intrinsic factors such as the type of chitosan, the degree of chitosan polymerization and extrinsic factors such as the microbial organism, the environmental conditions and presence of the other components. The use of chitosan in food systems should be based on sufficient knowledge of the complex mechanisms of its antimicrobial mode of action. In this article we review a number of studies on the investigation of chitosan antimicrobial properties and application of them in culture and food mediums. : {"references": ["S. Arcidiacono, and D. L. Kaplan, \"Molecular weight distribution of\nchitosan isolated from Mucor rouxii under different culture and\nprocessing conditions,\" Biotechnology and Bioengineering, vol. 39, pp.\n281-286, 1992.", "S. Chatterjee, M. Adhya, A. K. Guha, and B. P. Chatterjee, \"Chitosan\nfrom Mucor rouxii: production and physico-chemical characterization,\"\nProcess Biochemistry, vol. 40, pp. 395-400, 2005.", "P. C. Srinivasa, and R. N. Tharanathan, \"Chitin/Chitosan \u00d4\u00c7\u00f6 Safe,\nEcofriendly Packaging Materials with Multiple Potential Uses,\" Food\nReviews International, vol. 23, no. 1, pp. 53-72, 2007.", "M. N. V. Ravikumar, \"A review of chitin and chitosan application.\nReactive Functional Polymer, vol. 46, pp. 1-27, 2000.", "N. Liu, X. G. Chen, H. J. Park, C. G. Liu, C. S. Liu, X. H. Meng, and L.\nJ. Yu, \"Effect of MW and concentration of chitosan on antibacterial\nactivity of Escherichia coli,\" Carbohydrate Polymers, vol. 64, pp. 60-65,\n2006.", "H. K. No, N. Y. Park, S. H. Lee, H. J. Hwang, and S. P. Meyers,\n\"Antibacterial activities of chitosans and chitosan oligomers with\ndifferent molecular weights on spoilage bacteria isolated from tofu,\"\nJournal of Food Science, vol. 67, no. 4, pp.1511-1514, 2002.", "H. Sashiwa and S. Aiba, \"Chemically modified chitin and chitosan as\nbiomaterials,\" Progress in Polymer Science, vol. 29, pp. 887-908, 2004.", "C. Qin, H. Li, Q. Xiao, Y. Liu, J. Zhu and Y. Du, \"Water-solubility of\nchitosan and its antimicrobial activity,\" Carbohydrate Polymers, vol. 63,\nno. 3, pp. 367-374, 2006.", "A. B. Mart\u251c\u00a1n-Diana, D. Rico, J. M. Barat, C. Barry-Ryan, \"Orange juices\nenriched with chitosan: Optimisation for extending the shelf-life,\"\nInnovative Food Science and Emerging Technologies, vol. 10, pp. 590-\n600, 2009.\n[10] V. Coma, A. Deschamps, and A. Martial-Gros, \"Bioactive packaging\nmaterials from edible chitosan polymer\u00d4\u00c7\u00f6Antimicrobial activity\nassessment on dairy-related contaminants, Journal of Food Science, vol.\n68, no. 9, pp. 2788-2792, 2003.\n[11] F. Devlieghere, A. Vermeulen, and J. Debevere, \"Chitosan:\nantimicrobial activity, interactions with food components and\napplicability as a coating on fruit and vegetables,\" Food Microbiology,\nvol. 21, pp. 703-714, 2004.\n[12] Y. C. Chung, Y. P. Su, C. C. Chen, G. Jia, H. L. Wang, J. C. G. Wu, and\nJ. G. Lin, \"Relationship between antibacterial activity of chitosan and\nsurface characteristics of cell wall,\" Acta Pharmacologica Sinica, vol.\n25, no. 7, pp. 932-936, July 2004.\n[13] D. Raafat, K. Bargen, A. Haas, and H. G. Sahl, \"Insights into the mode\nof action of chitosan as an antibacterial compound,\" Appied and\nEnvironmental Microbiology, vol. 74, no. 12. pp. 3764-3773, June\n2008.\n[14] Y. J. Jeon, and S. K. Kim, \"Production of chitooligosaccharides using an\nultrafiltration membrane reactor and their antibacterial activity,\"\nCarbohydrate Polymers, vol. 41, pp. 133-144, 2000.\n[15] Y.Omura, M. Shigemoto, T. Akiyama, H. Saimoto, Y. Shigemasa, I.\nNakamura, T. Tsuchido, \"Reexamination of antimicrobial activity of\nchitosan having different degrees of acetylation and molecular weights,\"\nAdvances in Chitin Science, vol. 6, pp. 273-274, 2002.\n[16] L. Y. Zheng,. and J. F. Zhu, \"Study on antimicrobial activity of chitosan\nwith different molecular weights,\" Carbohydrate Polymers, vol. 54, pp.\n527-530, 2003.\n[17] D. Raafat and H. G. Sahl, \"Chitosan and its antimicrobial potential - a\ncritical literature survey,\" Microbial Biotechnology, vol. 2, no. 2, pp.\n186-201, 2009.\n[18] R. C. Goy, D. Britto, O. B. G. Assis, \"A review of the antimicrobial\nactivity of chitosan.,\" Pol\u251c\u00a1meros: Ci\u251c\u00acncia e Tecnologia, vol. 19, no 3, pp.\n241-247, 2009.\n[19] T. C.Yang, C. C. Chou, and C. F. Li, \"Preparation, water solubility and\nrheological property of the N-alkylated mono or disaccharide chitosan\nderivatives,\" Food Research International, vol. 35, pp. 707- 713, 2002.\n[20] T. C. Yang, C. C. Chou, and C. F. Li, \"Antibacterial activity of Nalkylated\ndisaccharide chitosan derivatives,\" International Journal of\nFood Microbiology, vol. 97, pp. 237- 245, 2005.\n[21] X. Li, X. Shi, M. Wang, and Y. Du, \"Xylan chitosan conjugate - a\npotential food preservative,\" Food Chemistry, vol. 126. no. 2, pp. 520-\n525, May 2011.\n[22] \u00d6. V. R\u00fanarsson, J. Holappa, T. Nevalainen, M. Hj\u00e1lmarsd\u00f3ttir, T.\nJ\u00e4rvinen, T. Loftsson, J. M. Einarsson, S. J\u00f3nsd\u00f3ttir, M. Valdimarsd\u00f3ttir,\nM. M\u251c\u00edsson, \"Antibacterial activity of methylated chitosan and\nchitooligomer derivatives: Synthesis and structure activity\nrelationships,\" European Polymer Journal, vol. 43, no. 6, pp. 2660-2671,\n2007.\n[23] N. Vallapa, O. Wiarachai, N. Thongchul, J. Pan, V. Tangpasuthadol, S.\nKiatkamjornwong and V. P. Hoven, \"Enhancing antibacterial activity of\nchitosan surface by heterogeneous quaternization,\" Carbohydrate\nPolymers, vol. 83, no. 2, pp. 868-875, 2011.\n[24] X. F. Liu, Y. L. Guan, D. Z. Yang, Z. Li, and K. D. Yao, \"Antibacterial\naction of chitosan and carboxymethylated chitosan,\" Journal of Applied\nPolymer Science, vol. 79, no. 7, pp. 1324-1335, 2000.\n[25] G. He, X. Chen, Y. Yin, H. Zheng, X. Xiong and Y. Du, \"Synthesis,\ncharacterization and antibacterial activity of salicyloyl chitosan,\"\nCarbohydrate Polymers, vol. 83, no. 3, pp. 1274-1278, Jan 2011.\n[26] Y. Feng, and W. Xia, \"Preparation, characterization and antibacterial\nactivity of water-soluble O-fumaryl-chitosan,\" Carbohydrate Polymers,\nvol. 83, no. 3, pp. 1169-1173, Jan 2011.\n[27] H. Tang, P. Zhang, T. L. Kieft, S. J. Ryan, S. M. Baker, W. P.\nWiesmann, and S. Rogelj, \"Antibacterial action of a novel functionalized\nchitosan-arginine against Gram-negative bacteria,\" Acta Biomaterialia,\nvol. 6, no. 7, pp. 2562-2571, 2010.\n[28] Y. Hu, Y. Du, J. Yang, J. F. Kennedy, X. Wang and L. Wang, \"Synthesis,\ncharacterization and antibacterial activity of guanidinylated chitosan,\"\nCarbohydrate Polymers, vol. 67, no. 1, pp. 66-72, 2007.\n[29] R. L. Beverlya, M. E. Janesa, W. Prinyawiwatkula, H. K. No, \"Edible\nchitosan films on ready-to-eat roast beef for the control of Listeria\nmonocytogenes,\" Food Microbiology, vol. 25, pp. 534-537, 2008.\n[30] R. Cao, C. H. Xue, and Q. Liu, \"Changes in microbial flora of Pacific\noysters (Crassostrea gigas) during refrigerated storage and its shelf-life\nextension by chitosan\" International Journal of Food Microbiology, vol.\n131, pp. 272-276, 2009.\n[31] K. W. Kim, B. J. Min, Y. T. Kim, R. M. Kimmel, K. Cooksey, and S. I.\nPark, \"Antimicrobial activity against foodborne pathogens of chitosan\nbiopolymer films of different molecular weights\" LWT - Food Science\nand Technology, vol. 44, pp. 565-569, 2011.\n[32] P. Chhabra, Y. W. Huang, J. F. Frank, R. Chmielewski, and K. Gates,\n\"Fate of staphylococcus aureus, salmonella enterica serovar\ntyphimurium, and vibiro vulnificus in raw oysters treated with chitosan,\"\nJournal of Food Protection, vol. 69, pp. 952-959, 2006.\n[33] S. Chaiyakosa, W. Charernjiratragul, K. Umsakul and V. Vuddhakul,\n\"Comparing the efficiency of chitosan with chlorine for reducing Vibrio\nparahaemolyticus in shrimp,\" Food Control, vol. 18, no. 9, pp.1031-\n1035, 2007.\n[34] S. M. A. Taha, and H. M. H. Swailam, \"Antibacterial activity of chitosan\nagainst Aeromonas hydrophila,\" Food / Nahrung, vol. 76, no. 5, pp. 337-\n340, 2002.\n[35] G. J. Tsai, M. T. Tsai, J. M. Lee, and M. Z. Zhong, \"Effects of chitosan\nand a low-molecular-weight chitosan an Bacillus cereus and application\nin the preservation of cooked rice,\" Journal of Food Protection, vol. 69,\nno. 9, pp. 2168-2175, 2006.\n[36] P. Fernandez-Saiz, C. Soler, J. M. Lagaron and M. J.Ocio, \"Effects of\nchitosan films on the growth of Listeria monocytogenes, Staphylococcus\naureus and Salmonella spp. in laboratory media and in fish soup,\"\nInternational Journal of Food Microbiology, vol. 137, no. 2, pp. 287-\n294, 2010.\n[37] M. Ye, H. Neetoo, H. Chen, \"Control of Listeria monocytogenes on ham\nsteaks by antimicrobials incorporated into chitosan-coated plastic films,\"\nFood Microbiology, vol. 25, no. 2, p. 260-268, 2008.\n[38] S. Roller, and N. Covill, \"The antifungal properties of chitosan in\nlaboratory media and apple juice,\" International Journal of Food\nMicrobiology, vol. 47, pp. 67-77, Mar 1999.\n[39] M. S. Rodr\u251c\u00a1guez, V. Ramos, and E. Agull\u251c\u2502, \"Antimicrobial action of\nchitosan against spoilage organisms in precooked pizza,\" Journal of\nFood Science, vol. 68, no. 1, pp. 271-274, 2006.\n[40] S. I. Park, K. S. Marsh, and P. Dawson, \"Application of chitosanincorporated\nLDPE film to sliced fresh red meats for shelf life\nextension,\" Meat Science, vol. 85, pp. 493-499, 2010.\n[41] R. D. Joerger, S. Sabesan, D. Visioli, D. Urian, and M. C. Joerger,\n\"Antimicrobial activity of chitosan attached to ethylene copolymer\nfilms,\" Packaging Technology and Science, vol. 22, no. 3, pp. 125-138,\n2008.\n[42] P. Fernandez-Saiz, M. J. Ocio, and J. M. Lagaron, \"Antibacterial\nchitosan-based blends with ethylene-vinyl alcohol copolymer,\"\nCarbohydrate Polymers, vol. 80, no. 3, pp. 874-884, 2010.\n[43] S. Tripathi, G. K. Mehrotra and P. K. Dutta, \"Physicochemical and\nbioactivity of cross-linked chitosan-PVA film for food packaging\napplications,\" International Journal of Biological Macromolecules, vol.\n45, no. 4, pp. 372-376, 2009.\n[44] F. Sebastien, G. Stephane, A. Copinet, and V. Coma, \"Novel\nbiodegradable films made from chitosan and poly(lactic acid) with\nantifungal properties against mycotoxinogen strains,\" Carbohydrate\nPolymers, vol. 65, pp.185-193, 2006.\n[45] F. Liu, B. Qin, L. He, and R. Song, \"Novel starch/chitosan blending\nmembrane: Antibacterial, permeable and mechanical properties,\"\nCarbohydrate Polymers. vol. 78, no. 1, pp. 146-150, 2009.\n[46] C. M. Shih, Y. T. Shieh and Y. K. Twu, \"Preparation and\ncharacterization of cellulose/chitosan blend films,\" Carbohydrate\nPolymers, vol. 78, no. 1, pp. 169-174, 2009.\n[47] M. E. Lopez-Caballero, M. C. Gomez-Guillen, M. Perez-Mateos and P.\nMontero, \"A chitosan-gelatin blend as a coating for fish patties,\" Food\nHydrocolloids, vol. 19, pp. 303-311, 2005.\n[48]L. Y. Sang, X. H. Zhou, F. Yun, and G. L. Zhang, \"Enzymatic synthesis\nof chitosan-gelatin antimicrobial copolymer and its characterization,\"\nJournal of the Science of Food and Agriculture, vol. 90, pp. 58-64,\n2010."]}